Phytoplankton dynamics in tropical biofloc-based whiteleg shrimp aquaculture - NUSHAIBA AZMA TAQIYYA; NANIK RETNO BUWONO; EVELLIN DEWI LUSIANA; MUHAMMAD MUSA (Society for Indonesian Biodiversity, 2026)
Abstract. Taqiyya NA, Buwono NR, Lusiana ED, Musa M. 2026. Phytoplankton dynamics in tropical biofloc-based whiteleg shrimp aquaculture. Biodiversitas 27 (7): d270711. https://doi.org/10.13057/biodiv/d270711. Biofloc Technology (BFT) has been used in whiteleg shrimp (Litopenaeus vannamei) aquaculture due to the higher sustainability compared to conventional intensive systems. In BFT ponds, microbial communities, particularly phytoplankton, are essential for nutrient cycling and water quality regulation, with their dynamics shaped by complex biotic and abiotic interactions. Phytoplankton composition and its connection to water quality are central to effective BFT management. This study assessed temporal changes in phytoplankton community structure using monthly observations at day of culture (DOC) 0, 30, 60, and 90 in a tropical biofloc-based whiteleg shrimp culture system. The study was conducted in three BFT aquaculture ponds in the coastal area of Indonesia, with repeated observations performed at four sampling times. Ten physicochemical water-quality parameters and phytoplankton community characteristics were monitored throughout the culture period. Exploration of the associations between water quality variables, phytoplankton communities, and biofloc characteristics was done using statistical approaches. The results showed that water quality in the BFT system was generally suitable for whiteleg shrimp culture; however, temperature, transparency, pH, ammonia, and nitrite occasionally exceeded or fell outside the recommended ranges reported for shrimp culture. Meanwhile, the structure of the phytoplankton community was dominated by Bacillariophyceae, Chlorophyceae, and Cyanophyceae. Temporal changes in water quality and phytoplankton community composition were observed throughout the culture period. Chlorophyceae and Dinophyceae were observed at relatively notable proportions during several observation periods, suggesting that variations in transparency, nitrite, and nitrate might be linked to differences in phytoplankton composition across DOC 0-90 in the ponds studied. These findings describe temporal patterns within a site-specific tropical biofloc-based shrimp culture system and may provide baseline information for future comparative studies.